Efeitos da tricostatina A sobre a acetilação de histonas, proliferação celular e diferenciação de células tronco embrionárias murinas - Oliveira, Clara Slade [UNESP]; Oliveira, Leticia Zoccolaro [UNESP]; Saraiva, Naiara Zoccal [UNESP]; Monteiro, Fabio Morato [UNESP]; Garcia, Joaquim Mansano [UNESP] (Universidade Federal do Rio Grande do Sul (UFRGS), 2011)
Background: Embryonic stem cells are cells derived from early-stage embryos that are characterized by pluripotency and self-renewal capacity. The in vitro cultured murine embryonic stem cells can indefinitely propagate in an undifferentiated state in the presence of leukemia inhibitory factor (LIF). However, when stimulated, these cells can differentiate into cell lines derived from all three embryonic germ layers. The trichostatin A (TSA) is an epigenetic modifier agent and several studies have used the TSA to stimulate cellular differentiation. However, most of these studies only assessed one TSA concentration. Therefore, this study aimed to evaluate the effects of different TSA concentrations on histone hyperacetylation during in vitro cell differentiation of murine pluripotent embryonic stem cells, cultured with or without LIF, in the quest of to standardize their application on early cultures of embryonic stem cells.Materials, Methods & Results: Undifferentiated murine embryonic stem cells were plated in the presence of different TSA concentrations (0 nM, 15 nm, 50 nM and 100 nM) in the presence or absence of LIF. Thus, the treatments were evaluated in undifferentiated embryonic stem cells cultured in the presence of LIF (Control group: 0 nM LIF(+); Group 15 nM LIF+; Group 50 nM LIF+ and Group 100 nM LIF+), and in embryonic stem cells cultured in the absence of LIF (Control group: 0 nM LIF; Group 15 nM LIF(-); Group 50 nM LIF(-) and Group 100 nM LIF-). Treatment with TSA was performed for 24 h. After that the medium was replaced with fresh medium without TSA. Samples were collected at 0, 12, 24, 36 and 48 h after the beginning of the experiment. Three replicates were performed in each experimental group. The relative amount of Histone H3 lysine 9 acetylation was analyzed in all groups, as well as the cell proliferation in the embryonic stem cells cultured in the presence of LIF. In the control group (0 nM), the absence of LIF resulted in higher levels (P < 0.05) of H3lys9ac compared to the cultures supplemented with LIF. In the embryonic stem cells cultured in the presence of LIF, the 50 nM and 100 nM treatments resulted in higher levels (P < 0.05) of H3lys9ac when compared with 0 nM and 15 nM treatments. Evaluating the Hoechst area in the 0 nM group, it was observed that the number of cells increased (P < 0.05) according to the time of culture. Treatment with 15 nM also reflected a similar distribution, but the Hoechst area in 15 nM group was lower (P < 0.05) at 24 and 48h when compared to the observed in the control group. In the 100 nM treatment, was observed that the area of Hoechst was lower (P < 0.05) to that obtained in the control group at 12, 24 and 48h. In addition, it was observed that treatment with TSA induces greater cellular differentiation when compared to control groups in stem cells cultured in the presence of LIF as well as in the absence of LIF.Discussion: In the present study it was observed that TSA treatment increased the levels of histone acetylation in murine embryonic stem cells at a 50 nM concentration, making it possible to reduce the concentration recommended in the literature (100 nM). In addtion, it was concluded that the lower TSA concentrations utilized (15 nm and 50 nM) was less harmful to cellular proliferation than the 100 nM TSA concentration.
Effects of Trichostatin A on Histone Acetylation, Cell Proliferation and Differentiation of Murine Embryonic Stem Cells
Keywords: Embryonic stem cells; histone acetylation; murine; trichostatin A